2004
DOI: 10.1103/physrevlett.92.237401
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Density Disturbances in Water with a 41.3-Attosecond Time Resolution

Abstract: We show that the momentum flexibility of inelastic x-ray scattering may be exploited to invert its loss function, alowing real time imaging of density disturbances in a medium. We show the disturbance arising from a point source in liquid water, with a resolution of 41.3 attoseconds (4.13 × 10 −17 sec) and 1.27Å (1.27×10 −8 cm). This result is used to determine the structure of the electron cloud around a photoexcited chromophore in solution, as well as the wake generated in water by a 9 MeV gold ion. We draw … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 27 publications
0
71
0
Order By: Relevance
“…This technique has been used to study a broad range of systems [27,28]. The recent development of Green's function imaging (GFI) [21,29,30] combined with high-intensity third generation synchrotron sources have allowed ultrafast movies at subangstrom spatial resolution to be made. In our IXS experiment [ Fig.…”
Section: Green's Function Imaging Of Dynamicsmentioning
confidence: 99%
“…This technique has been used to study a broad range of systems [27,28]. The recent development of Green's function imaging (GFI) [21,29,30] combined with high-intensity third generation synchrotron sources have allowed ultrafast movies at subangstrom spatial resolution to be made. In our IXS experiment [ Fig.…”
Section: Green's Function Imaging Of Dynamicsmentioning
confidence: 99%
“…[6,4] If successfully implemented, this approach would reveal the complete density response, χ(x 1 , x 2 , t), which describes the electron disturbance created by a source placed at any arbitrary location, Analyzing a simple model of a single quantum particle in a periodic potential, we have shown that standing wave IXS imaging is an innately three-dimensional measurement, in the sense that both out-of-plane analyzer motions and sample Ψ-rotations are required to achieve a complete data set. Such an experiment would require (at the minimum) two copies of the crystal of interest: one that is asymmetrically cut to collimate the beam, and a second to create the standing wave field and function as the "sample".…”
Section: Discussionmentioning
confidence: 99%
“…[4] However, it provides explicit, real-space images, and contains no intrinsic limit on the achievable time resolution: attosecond or even zeptosecond resolution is achievable. So far, IXS imaging has been used to study collective electron dynamics in liquid water, [6,7] excitons in large-gap insulators, [8] and to measure the effective fine structure constant of graphene. [9] Up to now, however, there has been a limitation on the imaging aspect of this approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a time-resolved measurement, where the pulse duration must be much shorter than the characteristic time of the electron dynamics, the incoming photon energy is not precisely defined, and the signal depends on the spectrum of the broadband probe pulse [36]. Spectrally resolved inelastic x-ray scattering from a stationary system encodes a dynamic structure factor, which can provide access to electron dynamics at the level of linear response theory [41,42]. Our method measures the state of an electron system at a given time independently from how this state had been created.…”
Section: B Qed Descriptionmentioning
confidence: 99%